12 Weeks of Kindergarten-Based Yoga Practice Increases Visual Attention, Visual-Motor Precision and Decreases Behavior of Inattention and Hyperactivity in 5-Year-Old Children - Jarraya, Sana; Wagner, Matthias; Jarraya, Mohamed; Engel, Florian A. (Frontiers in Psychology, 2019)
The present study assesses the impact of Kindergarten-based yoga on cognitive performance, visual-motor coordination, and behavior of inattention and hyperactivity in 5-year-old children. In this randomized controlled trial, 45 children (28 female; 17 male; 5.2 ± 0.4 years) participated. Over 12 weeks, 15 children performed Hatha-yoga twice a week for 30 min, another 15 children performed generic physical education (PE) twice a week for 30 min, and 15 children performed no kind of physical activities, serving as control group (CG). Prior to (T0) and after 12 weeks (T1), all participants completed Visual Attention and Visuomotor Precision subtests of Neuropsychological Evaluation Battery and teachers evaluated children’s behavior of inattention and hyperactivity with the Attention-Deficit/Hyperactivity Disorder (ADHD) Rating Scale-IV. At T0, no significant differences between groups appeared. Repeated measures analysis of variance revealed that following Bonferroni–Holm corrections yoga, in comparison to PE and CG, had a significant positive impact on the development on behavior of inattention and hyperactivity. Further, yoga has a significant positive impact on completion times in two visumotor precision tasks in comparison to PE. Finally, results indicate a significant positive effect of yoga on visual attention scores in comparison to CG. 12 weeks of Kindergarten-based yoga improves selected visual attention and visual-motor precision parameters and decreases behavior of inattention and hyperactivity in 5-year-old children. Consequently, yoga represents a sufficient and cost-benefit effective exercise which could enhance cognitive and behavioral factors relevant for learning and academic achievement among young children.